The Origins and Dynamics of Export Superstars - Freund, Caroline; Pierola, Martha Denisse (Published by Oxford University Press on behalf of the World Bank, 2021)
Export superstars are important for export growth and diversification and are typically born large. Firm-level data on manufacturing trade from 32 developing countries show that the top five exporters account for on average nearly one-third of exports, 47 percent of export growth, and a third of the growth due to export diversification over a five-year period. Within countries and industries, export growth is positively correlated with the share of exports in the top five firms. Most of the top five exporters were already large five (or eight) years ago or are new firms; it is rare for these export superstars to emerge from the bottom half of the distribution of firm sizes. For countries where detailed data exist, superstars are producers, not traders, and are primarily foreign owned.